The fame monster pastiche versus parody in the context of surplus economy - Macapagal, Katrina Angela R.
"... distinguishes the logic of pastiche from that of parody and how the aesthetics of both are seen in the videos of American performance artist, Lady Gaga and her local counterpart, Lady Gagita." -- Introduction
Keywords: Pasticcio; Parody in music; Performance art -- social aspects; Cross-cultural differences